ANALISIS PENGELOLAAN PIUTANG SEBAGAI TINDAK LANJUT KEBIJAKAN PENJUALAN KREDIT - Wardiningsih, Suprihatmi Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2011)
ABSTRACT With increasing competition in the business world, requires companies increase product sales policies, which need to offer product sales on credit in addition to product sales in cash. With a sales volume of credit sales are expected to increase by leaps and bounds, so the profit is also increasing. Accounts receivable arising as a credit sale occurs, and simultaneously it also costs incurred in the management of accounts receivable include: the cost of investment in accounts receivable, cash discount, the cost of bad debts and so on. Receivables must be managed efficiently, because it involves the profits and costs incurred because of the receivables. The policy should be managed optimally receivables which means that every element of the policy should consider the benefits of accounts receivable and sacrifice. As far as the benefits outweigh the costs then a decision is economically justified. Keywords: credit sales, accounts receivable, benefits, costs